Sustainable investments: assessment of risks - Kaab Omeir, Ahmad; Štreimikienė, Dalia; Vasiliauskaitė, Deimantė (Journal of Business Economics and Management, 2025)
Sustainable investments become a more and more relevant topic in all fields of economics. It is essential to measure both the benefits of sustainable products and risks. This article examines the risks associated with sustainable investments, mainly focusing on green bonds. It highlights financial institutions’ increasing interest in sustainable asset management, including central banks. The study addresses the complexity of integrating climate risk into existing risk management frameworks and the lack of tools for estimating and managing these effects. This research aims to measure the volatility of different fixed-income financial instruments, trying to identify which GARCH model is the best. Our research utilizes Bloomberg data from eight sustainable corporate fixed-income indices. The study’s sample comprises sustainable investment indices within the fixed-income market, selected based on data availability and the representativeness of the asset class. The dataset includes daily closing prices and daily returns of these indices, covering a unified sample period from July 25, 2019, to September 28, 2022. The models used for the research are ARCH, GARCH, TGARCH, EGARCH, and PARCH. The results show that sustainable investments are not risk-free, emphasizing the need for comprehensive risk assessment and management. From the applied models, the results show that the PARCH model is the best for fixed-income indices volatility modeling.